Characteristics of MicroRNA Expression Depending on the Presence or Absence of Meningioma in Patients with Neurofibromatosis Type 2: A Secondary Analysis - HORIE, Nobutaka; MITSUHARA, Takafumi; IMURA, Takeshi (Neurologia Medico-Chirurgica, 2024)
Meningioma is the second most frequent tumor in patients with neurofibromatosis type 2 (NF2). The presence of meningioma is believed to be a negative prognostic marker in these patients. However, the molecular mechanisms involved in the tumorigenesis of NF2-associated meningioma are not well characterized. Epigenetic regulation, including microRNAs (miRNAs), may be involved in the development of different tumor types in patients with NF2. The objective of this study is to explore the different characteristics of serum miRNA expression depending on the presence or absence of meningioma in patients with NF2. Nine patients with NF2 who were treated at the Department of Neurosurgery, Hiroshima University Hospital, were included. Total RNA (including small RNAs) was extracted from serum samples for the preparation of a small RNA library for next-generation sequencing analysis. Differentially expressed miRNAs (DEMs) were analyzed using the DESeq2 package to compare the characteristic miRNA expression profiles of patients with and without meningioma. In small RNA sequencing analysis, out of a total of 1,879 miRNAs registered in the database, the expressions of 657 miRNAs were observed. In DEM analysis, the expressions of four miRNAs, namely, hsa-miR-664b, hsa-miR-7706, hsa-miR-590, and hsa-miR-6513, were downregulated in patients with NF2 with meningioma compared with patients with NF2 without meningioma. Hsa-miR-193a was identified as the only upregulated miRNA in patients with NF2 with meningioma. In conclusion, we identified different circulating miRNA expression characteristics depending on the presence or absence of meningioma in patients with NF2.